How smart senior care can achieve value co-creation: Evidence from China - Fu, Liping; Pei, Tong; Yang, Jie; Han, Jiarui (Frontiers in Public Health, 2022)
With the rapid rise of artificial intelligence, smart senior care has become a new trend for future development. The collection of "Typical Cases of Chinese Elderly Service Industry Development" is selected by the script materials. The main purpose of this article is to investigate how smart senior care can achieve value co-creation by grounded theory. This study explores the phenomenon of value co-creation in the participation of multiple actors in smart senior care services. Findings show that institutional guarantee, technical intake, market empowerment, emotional support, service interaction, and reciprocity norm are identified as the driving factors for value co-creation. In addition, the behavioral processes of value co-creation include multi-actor value consensus, co-creation environment establishment, practical value co-creation, public value sharing, and diffusion of service added value in smart senior care. Finally, this study constructs a practical logic model of achieving value co-creation. It extends and enriches the scope of the value co-creation theory. This study confirms that value co-creation can be effectively achieved in smart senior care by the above-mentioned ways, revealing its driving factors and behavioral processes. The article expands on the application of value co-creation in the field of public healthcare. The results have important theoretical and practical significance for narrowing the public service equalization gap.